Sunday

March 29, 2015

March 29, 2015

Posted by **Claure** on Tuesday, June 16, 2009 at 7:57pm.

How do I find the x-intercept for this?

This is from my book:

step 1: 0=x^3-4x^2-x+4

step 2: 0=x^2(x-4)+(-1)(x-4)

step 3: 0=(x^2-1)(x-4)

I know how to solve once I get to step 3, but in step 2, I don't know what they've done or why. Where does that (-1) come from? Why is it (x-4)?

Please help explain this to me. I'd be really thankful.

- Algebra help -
**Damon**, Tuesday, June 16, 2009 at 8:07pmstep 1: 0=x^3-4x^2-x+4

we would like to factor that.

rewrite as

x^3-4x^2 - (x-4)

now you can see that I can factor an (x-4) out of the first two terms

x^2 (x-4) - (x-4)

which is

x^2 (x-4) -1 (x-4)

step 2: 0=x^2(x-4)+(-1)(x-4)

step 3: 0=(x^2-1)(x-4)

**Answer this Question**

**Related Questions**

ALGEBRA HELP - When solving the equation, what property was used to go from step...

pre algebra - solve the equation step by step.list each step along with the ...

Algebra 1--Step-by-Step - Can someone show me how to solve these step-by-step? ...

Quick math help - In which step below does a mistake first appear in simplifying...

algerbra - solve the equation step by step list each step along with the ...

algebra 1 - ELEMENTARY ALGEBRA #3 Page 23 Chapter 3 Lesson 3.02 Solving Multi-...

Algebra - Debbie finished her algebra test early so she decided to check each of...

Algebra - How do I solve for the elimination method: 5x + 3y= -7 and 7x - 2y =13...

Math - Step 1 = 3 boxes Step 2 = 6 boxes Step 3 = 11 boxes Step 4 = 18 boxes How...

english! - Make sure you understand the topic(s) is a step in the research ...